A STUDY ON ANTHROPOMETRIC MEASUREMENTS AND CLINICAL IMPLICATIONS OF AIDS PATIENTS - HARIKA, V. CHINNARI; SUNITHA, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
The HIV/AIDS is a slow onset disaster, which means a threatening hazard, is causing serious disruption on all aspects of societies life and progress. For the purpose of information pathological condition, clinical implications and Anthropometric measurements were selected. The mean weight of normal subjects is 59.60kg and the height is 167.30cm. these normal subjects showed normal height and weights and the AIDS patients showed 7 kg. lower weight and height as per the ICMR norms. 60% people are reporting that they had clinical complications. Around 33-49% both females and males complained of joint pains.